SHARING ECONOMY AND INCLUSIVE TOURISM DEVELOPMENT: A CASE STUDY ON THE WATERBERG DISTRICT IN SOUTH AFRICA - Refiloe Julia LEKGAU; Tracy DANIELS; Tembi Maloney TICHAAWA (Geo Journal of Tourism and Geosites)
The purpose of the study was to analyse inclusive tourism development in the Global South, using a case study of Airbnb’s interventions in the Waterberg District of South Africa. Adopting a qualitative approach, the research was conducted in three phases. The first phase consisted of a focus group held with Airbnb representatives who were involved in the planning and operations of the programme. The second and third phases involved in-depth interviews with Airbnb partners and graduates of the Airbnb Academy, respectively. The findings reveal that previously excluded groups were able to become tourism producers, through the skills development programme, joining the Airbnb app, and the tangible outcomes from the interventions. The programme also widened the scope of opportunities for members who previously did not identify as part of the tourism value chain. Further, there was a notable change in the tourism landscape, now involving experiences that are more authentic and representative of the culture and lifestyle of the community. However, the tourism industry is prevalently white-owned, presenting substantial challenges for graduates of the programme to tap into the tourism market. The findings confirm that inclusive tourism is intrinsically embedded in the local context: politics, economy, and society. In this regard, the study expands and contextualises the literature on inclusive tourism development in the Global South.